Online water monitoring system in Malaysia: An overall assessment / Iffa Munira Mohd Mizan - Iffa Munira, Mohd Mizan (2022)
Water monitoring is identifiable as a systematic analysis of water quality to identify and notify us of the current and ongoing status of the water bodies. It also highlighted emerging problems and the countermeasure that should contemplate in managing water quality. Water is not only crucial for industrial uses but also domestic usage. Untreated water can affect the ecosystem of living and non-living organisms. There are several methods of identifying the contaminants in the water bodies, such as the conventional approach and online water monitoring. The type of water monitoring implemented in Malaysia are manual water quality monitoring and continuous monitoring. There are only 15 stations for continuous monitoring, while there are almost 2000 stations for conventional monitoring. This research aims to propose the best online water monitoring model for Malaysia. Online water monitoring implements current technology such as sensors to identify contaminants that have disturbed the water elements' properties. This study aims to access the current online water monitoring practice in Malaysia and determine the best systems for online water monitoring based on the best practices. The data obtained in this research are from secondary data of the studies conducted in other countries. This particular data was chosen based on the technology and capabilities to be carried out in Malaysia. This work presents an analysis of recent works carried out in the system of online water monitoring. Also, best practices of online water quality monitoring based on the Internet of Things (IoT) method. The model developed is used in identifying the water sample, and data transmit in the cloud/internet/systems are analyzed. Water parameters such as color, odor, taste, and bacterial value are discussed as indicators to analyze water quality. In addition, federal and state government plays a significant role in managing water monitoring as they are the policymakers and the regulatory authorities.